Ответ:
[tex]\frac{c-x}{3}[/tex]
Пошаговое объяснение:
[tex](c+x-\frac{2cx}{x+c})*\frac{c^2-x^2}{3c^2+3x^2}=\\\\=\frac{(x+c)^2-2cx}{x+c}*\frac{(c-x)(c+x)}{3(c^2+x^2)}=\\\\=\frac{x^2+c^2+2xc-2cx}{1}*\frac{c-x}{3(c^2+x^2)}=\\\\=\frac{(x^2+c^2)(c-x)}{3(c^2+x^2)}=\\\\=\frac{c-x}{3}[/tex]
Формулы для решения:
[tex]a^2-b^2=(a-b)(a+b)\\\\(a+b)^2=a^2+b^2+2ab[/tex]
(c+x-2cx/x+c)*c²-x²?3c²+3x²
c*(x+c)+x*(x+c)-2cx/x+c*(c-x)*(c+x)/3(c²+x²)
(cx+c²+x²+cx)*c-x/3(c²+x²)
(0+c²+x²)*c-x/3(c²+x²)
(c²+x²)*x/3(c²+x²)
c-x/3
( o=^•ェ•)o ┏━┓
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]\frac{c-x}{3}[/tex]
Пошаговое объяснение:
[tex](c+x-\frac{2cx}{x+c})*\frac{c^2-x^2}{3c^2+3x^2}=\\\\=\frac{(x+c)^2-2cx}{x+c}*\frac{(c-x)(c+x)}{3(c^2+x^2)}=\\\\=\frac{x^2+c^2+2xc-2cx}{1}*\frac{c-x}{3(c^2+x^2)}=\\\\=\frac{(x^2+c^2)(c-x)}{3(c^2+x^2)}=\\\\=\frac{c-x}{3}[/tex]
Формулы для решения:
[tex]a^2-b^2=(a-b)(a+b)\\\\(a+b)^2=a^2+b^2+2ab[/tex]
(c+x-2cx/x+c)*c²-x²?3c²+3x²
c*(x+c)+x*(x+c)-2cx/x+c*(c-x)*(c+x)/3(c²+x²)
(cx+c²+x²+cx)*c-x/3(c²+x²)
(0+c²+x²)*c-x/3(c²+x²)
(c²+x²)*x/3(c²+x²)
c-x/3
( o=^•ェ•)o ┏━┓